2017
DOI: 10.1101/174185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YAP and TAZ regulate adherens junction dynamics and endothelial cell distribution during vascular development

Abstract: 51signaling to balance endothelial cell distribution in angiogenic vessels.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 54 publications
(60 reference statements)
7
68
0
Order By: Relevance
“…Lipid phosphate phosphatase 3 (LPP3) is an ectoenzyme expressed on the surface of ECs and seems to contribute predominantly to the degradation of LPA in blood (63). Yukiura et al reported that LPP3 is expressed locally in HUVECs, i.e., LPP3 is localized results in HUVECs (36), it is noteworthy that the Notch inhibitor DAPT restored the sprouting defects of YAP/TAZ siRNA-treated HUVECs in our study. YAP/TAZ-mediated DLL4 suppression is likely to be involved in LPA4/LPA6-mediated sprouting angiogenesis, as DAPT again restored sprouting defects in LPA4/LPA6 siRNA-treated HUVECs.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Lipid phosphate phosphatase 3 (LPP3) is an ectoenzyme expressed on the surface of ECs and seems to contribute predominantly to the degradation of LPA in blood (63). Yukiura et al reported that LPP3 is expressed locally in HUVECs, i.e., LPP3 is localized results in HUVECs (36), it is noteworthy that the Notch inhibitor DAPT restored the sprouting defects of YAP/TAZ siRNA-treated HUVECs in our study. YAP/TAZ-mediated DLL4 suppression is likely to be involved in LPA4/LPA6-mediated sprouting angiogenesis, as DAPT again restored sprouting defects in LPA4/LPA6 siRNA-treated HUVECs.…”
Section: Discussionsupporting
confidence: 67%
“…YAP nuclear localization was impaired in the angiogenic front of Lpa4;Lpa6 iΔEC retinas. Several independent studies have revealed that endothelial YAP/TAZ mediate sprouting angiogenesis (31)(32)(33)(34)(35)(36). In this context, we propose LPA4 and LPA6 as regulators of sprouting angiogenesis that repress DLL4 expression by activating YAP/TAZ in ECs.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The nuclear localization and thus the strength of YAP/TAZ signaling depends on ECM rigidity and actin stress fiber formation (Dupont et al, 2011). Recent experiments revealed that the ECM stiffness-dependent regulation of YAP/TAZ localization is also sensitive to the density and spacing of integrin receptors (Oria et al, 2017), while an independent study identified a role of YAP/TAZ in regulating the stability of AJs through modulation of BMP signaling (Neto et al, 2018). It has been also speculated that nuclear entry of YAP is modulated by force-dependent regulation of nuclear pores (Elosegui-Artola et al, 2017).…”
Section: Crosstalk Through Common Adaptor Proteins and Mechano-chemicmentioning
confidence: 99%